Mobile applications for the promotion and support of healthy nutrition and physical activity habits: A systematic review, extraction of features and taxonomy proposal - Villasana, María Vanessa; Pires, Ivan Miguel; Sá, Juliana; Garcia, Nuno M; Zdravevski, Eftim; CHorbev, Ivan; Lameski, Petre; Flórez-Revuelta, Francisco (My University, 2019)
Background: Mobile applications can be used for the monitoring of lifestyles and physical activity. It can be installed in commodity mobile devices, which are currently used by different types of people in their daily activities worlwide . Objective: This paper reviews and categorizes the mobile applications related to diet, nutrition, health, physical activity and education, showing the analysis of 73 mobile applications available on Google Play Store with the extraction of the different features. Methods: The mobile applications were analyzed in relation to each proposed category and their features, starting with the definition of the search keywords used in the Google Play Store. Each mobile application was installed on a smartphone, and validated whether it was researched in scientific studies. Finally, all mobile applications and features were categorized. Results: These mobile applications were clustered into four groups, including diet and nutrition, health, physical activity and education. The features of mobile applications were also categorized into six groups, including diet, anthropometric parameters, social, physical activity, medical parameters and vital parameters. The most available features of the mobile applications are weight, height, age, gender, goals, calories needed calculation, diet diary, food database with calories, calories burned and calorie intake. Conclusion: With this review, it was concluded that most mobile applications available in the market are related to diet, and they are important for different types of people. A promising idea for future work is to evaluate the acceptance by young people of such mobile applications.
Keywords: Nutrition, Physical activity, Mobile applications, Health, Systematic review, Diet, Google Play Store